Should the C4D expert survive? Rethinking expertise in communication and innovation. Issue 3 (3rd April 2018) - Noske-Turner, Jessica
ABSTRACT: The notion of expertise in communication for development (C4D) is a complicated matter. While C4D is ideally framed as inter-disciplinary, this comes into conflict with the need to define and maintain boundaries around C4D expertise within organisations and agencies. In this viewpoint these tensions are unpacked with reference to recent ethnographies of aid and development institutions, and expanded upon by a reflection on intersections between C4D and the rising interest in innovation for development. The viewpoint proposes "communication for innovation", or "communicative innovation" as an urgent new research agenda for C4D.